Atmospheric implications of the lack of H3+ detection at Neptune. (9th November 2020) - Moore, L.; Moses, J. I.; Melin, H.; Stallard, T. S.; O'Donoghue, J.
Abstract : H3 + has been detected at all of the solar system giant planets aside from Neptune. Current observational upper limits imply that there is far less H3 + emission at Neptune than rudimentary modelling would suggest. Here, we explore via modelling a range of atmospheric conditions in order to find some that could be consistent with observational constraints. In particular, we consider that the upper atmosphere might be much cooler than it was during the 1989 Voyager 2 encounter, and we examine the impact of an enhanced influx of external material that could act to reduce H3 + density. Resulting ionosphere models that are consistent with existing H3 + observational constraints have an exospheric temperature of 450 K or less, 300 K lower than the Voyager 2 value. Alternatively, if a topside CO influx of 2 × 10 8  cm −2  s −1 is imposed, the upper atmospheric temperature can be higher, up to 550 K. The potential cooling of Neptune's atmosphere is relevant for poorly understood giant planet thermospheric energetics, and would also impact aerobreaking manoeuvers for any future spacecraft. Such a large CO influx, if present, could imply Triton is a very active moon with prominent atmospheric escape, and/or that Neptune's rings significantly modify its upper atmosphere, and the introduction of so much exogenic material would complicate interpretation of the origin of species observed in Neptune's lower atmosphere. This article is part a discussion meeting issue 'Future exploration of ice giant systems'.